Suppression of Arabidopsis Mediator Subunit-Encoding MED18 Confers Broad Resistance Against DNA and RNA Viruses While MED25 Is Required for Virus Defense - Hussein, Nasser K.; Sabr, Layla J.; Lobo, Edina; Booth, James; Ariens, Emily; Detchanamurthy, Swaminathan; Schenk, Peer M. (Frontiers in Plant Science, 2020)
Mediator subunits play key roles in numerous physiological pathways and developmental processes in plants. Arabidopsis Mediator subunits, MED18 and MED25, have previously been shown to modulate disease resistance against fungal and bacterial pathogens through their role in jasmonic acid (JA) signaling. In this study, Arabidopsis mutant plants of the two Mediator subunits, med18 and med25, were tested against three ssRNA viruses and one dsDNA virus belonging to four different families: Turnip mosaic virus (TuMV), Cauliflower mosaic virus (CaMV), Alternanthera mosaic virus (AltMV) and Cucumber mosaic virus (CMV). Although both subunits are utilized in JA signaling, they occupy different positions (Head and Tail domain, respectively) in the Mediator complex and their absence affected virus infection differently. Arabidopsis med18 plants displayed increased resistance to RNA viral infection and a trend against the DNA virus, while med25 mutants displayed increased susceptibility to all viruses tested at 2 and 14 days post inoculations. Defense marker gene expression profiling of mock- and virus-inoculated plants showed that med18 and med25 mutants exhibited an upregulated SA pathway upon virus infection at 2 dpi for all viruses tested. JA signaling was also suppressed in med18 plants after virus infection, independent of which virus infected the plants. The upregulation of SA signaling and suppression of JA signaling in med18 may have led to more targeted oxidative burst and programmed cell death to control viruses. However, the susceptibility exhibited by med25 mutants suggests that other factors, such as a weakened RNAi pathway, might play a role in the observed susceptibility. We conclude that MED18 and MED25 have clear and opposite effects on accumulation of plant viruses. MED18 is required for normal virus infection, while MED25 is important for defense against virus infection. Results from this study provide a better understanding of the role of Mediator subunits during plant-virus interactions, viral disease progression and strategies to develop virus resistant plants.